2021
DOI: 10.37506/mlu.v21i2.2901
|View full text |Cite
|
Sign up to set email alerts
|

Conicity Index as an Anthropometric Index of Central Obesity in the Prediction of Adult Bronchial Asthma; Correlation with Fractional Exhaled Nitrous Oxide Tests

Amjed H. Abbas,
Hayder Abdul-Amir Al-Hindy,
Shahlaa Kh. Chabuk
et al.

Abstract: Obesity and bronchial asthma (BA) are two major health concerns. These entities have been further established by several meta-analyses. Still, these analyses denote to ''general-obesity'', that classically measured via body mass index (BMI), which is a broad measure unable to distinguish between lean musclebulk and body fats. Thus, other indices, should applied like waist perimeter, waist/hip ratio, and conicity index (CI), which are also reasonable, and normalized easily. Sufficient studies on the BA associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Testosterone and contraceptive pill use are inversely associated with sputum %neutrophils in adults with asthma, while CRP and IL-6 are associated with higher sputum %neutrophils 99. While the literature therefore suggests sex and sex hormones may be influencing the association between obesity, inflammation and adipokines in adults with asthma, we were unable to investigate this in the meta-analysis as only three studies reported sex effects,73 75 while four studies recruited only women64 69 76 78 and one study recruited only men 62. Given the existing research implicating sex and sex hormones in obesity-associated asthma, it is crucial that future studies examine how these influence airway and systemic inflammation, adipokines and clinical asthma outcomes in this population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Testosterone and contraceptive pill use are inversely associated with sputum %neutrophils in adults with asthma, while CRP and IL-6 are associated with higher sputum %neutrophils 99. While the literature therefore suggests sex and sex hormones may be influencing the association between obesity, inflammation and adipokines in adults with asthma, we were unable to investigate this in the meta-analysis as only three studies reported sex effects,73 75 while four studies recruited only women64 69 76 78 and one study recruited only men 62. Given the existing research implicating sex and sex hormones in obesity-associated asthma, it is crucial that future studies examine how these influence airway and systemic inflammation, adipokines and clinical asthma outcomes in this population.…”
Section: Discussionmentioning
confidence: 90%
“…The publication year ranged from 2006 to 2021. Sixteen articles (33%) were from America and Canada,33–48 14 (29%) were from Europe,49–61 11 (23%) were from Asia,62–72 five (10%) were from Australia and New Zealand,73–77 one (2%) was from Africa78 and one (2%) was from South America 79. Asthma was diagnosed by a physician and confirmed by variable airflow obstruction (airway hyper-responsiveness and/or bronchodilator reversibility) in 25 (52%) articles, physician-diagnosed in 19 (40%) articles, diagnosed as coded in a database in one (2%) article, and the method of asthma diagnosis was not reported in three (6%) articles.…”
Section: Resultsmentioning
confidence: 99%
“…As well, Another study that included 100 healthy controls and 116 males with AGA indicated that the patient's BMI was higher than that of the control group (36). Furthermore, it is widely acknowledged that obesity plays a role in immunoregulation (37).…”
Section: Evaluating the Role Of Thyroid Stimulating Hormone And Ferri...mentioning
confidence: 99%